Our Friend Hedgehog: A Place to Call Home - Castillo, Lauren (New York : Alfred A. Knopf, 2022)
"Hedgehog and her friends discover that home can be found in unexpected places"--
"This is a Borzoi book"--Title page verso.
Ages 5-9.
Keywords: Hedgehogs -- Juvenile fiction; Best friends -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Hedgehogs -- Fiction; Best friends -- Fiction; Animals -- Fiction; Friendship -- Fiction; Animal fiction